North-Atlantic dynamics and European temperature extremes in the IPSL model: Sensitivity to atmospheric resolution (2012)
The variability of the European climate is mostly controlled by the unstable nature of the North-Atlantic dynamics, especially in wintertime. The intra-seasonal to inter-annual fluctuations of atmospheric circulations has often been described as the alternation between a limited number of preferential weather regimes. Such discrete description can be justified by the multi-modality of the latitudinal position of the jet stream. In addition, seasonal extremes in European temperatures are generally associated with an exceptional persistence into one weather regime. Here we investigate the skill of the IPSL model to both simulate North-Atlantic weather regimes and European temperature extremes, including summer heat waves and winter cold spells. We use a set of eight IPSL experiments, with six different horizontal resolutions and the two versions used in CMIP3 and CMIP5. We find that despite a substantial deficit in the simulated poleward peak of the jet stream, the IPSL model represents weather regimes fairly well. A significant improvement is found for all horizontal resolutions higher than the one used in CMIP3, while the increase in vertical resolution included in the CMIP5 version tends to improve the wintertime dynamics. In addition to a recurrent cold bias over Europe, the IPSL model generally overestimates (underestimates) the indices of winter cold spells (summer heat waves) such as frequencies or durations. We find that the increase in horizontal resolution almost always improves these statistics, while the influence of vertical resolution is less clear. Overall, the CMIP5 version of the IPSL model appears to carry promising improvements in the simulation of the European climate variability.